Short-Term Load Forecasting Based on Complementary Ensemble Empirical Mode Decomposition and Long Short-Term Memory - Huiru ZHAO; Yihang ZHAO; Sen GUO (Zhongguo dianli)
With the continuous development of power industry, the importance of load forecasting is becoming more and more obvious. As an important part of load forecasting, short-term load forecasting is of great significance to the dispatching and operation of power system and market transactions. Accurate load forecasting is helpful to improve the utilization rate of power generation equipment and the effectiveness of economic dispatching. Because load data are affected by many random factors and have strong nonlinear characteristics, a short-term power load forecasting method is proposed based on complementary ensemble empirical mode decomposition and long short-term memory. A simulation is made of a city’s power load data using the proposed method, and the simulation results are compared with those of other traditional forecasting methods. It is proved that the long short-term memory model has lower error and higher prediction accuracy. At the same time, the prediction results of complementary ensemble empirical mode decomposition and long short-term memory are compared with those of long short-term memory model under other decomposition methods, which has verified that the complementary ensemble empirical mode decomposition method is effective in improving the prediction accuracy.